A stich in time: the story of Konark Cinema - Rajeev Kumar Panda; Swagatika Sahoo (Journal of Global Entrepreneurship Research, 2016)
The case describes the dramatic journey of a movie theater "Konark Cinema" from an oligopolistic to monopolistic competition, with an enormous opportunity to skim the market today. The primary concern for the owner and management is to revive the business in order to recover the huge losses, and to prepare the organization to meet the challenges from organized and unorganized sectors. The top management of Konark Cinema now has to focus on overhauling the company's strategy in order to improve service quality to achieve sustainable profitability. The issue requires urgent attention since as the overall company performance is deteriorating with every passing day making the situation even worse.
Keywords: 650; Entertainment industry; Repositioning; Market dynamics; Competitive strategy; Differentiation